2017
DOI: 10.1007/s41887-017-0008-9
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Escalation of Intimate Partner Violence: Evidence from 52,000 Offenders

Abstract: Research Question Does the severity or frequency of intimate partner violence or abuse reported to police increase over time, once a unique perpetrator-victim couple has come into contact with police in Thames Valley, UK? Data A total of 140,998 recent (non-historical) incidents of intimate partner violence or abuse reported to Thames Valley Police in 2010-2015 were identified, with 52,296 unique perpetrators for whom a standard 731-day observation period was possible after each perpetrator's first incident wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
30
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 13 publications
9
30
0
1
Order By: Relevance
“…It has, for example, examined overall offending in domestic abuse for any evidence of escalation in severity of harm inflicted against victims. Neither Bland and Ariel (2015) nor Barnham et al (2017) found any pattern of escalation in harm of domestic crime among abusers repeatedly reported to police. Where there is evidence of re-offending from these cohorts, average crime harm scores did not exceed the first-year average crime harm score; in fact, these power few offenders, as the studies described them, showed de-escalation in the severity of their offending.…”
Section: Using Crime Harm Indices To Track Offendersmentioning
confidence: 77%
See 2 more Smart Citations
“…It has, for example, examined overall offending in domestic abuse for any evidence of escalation in severity of harm inflicted against victims. Neither Bland and Ariel (2015) nor Barnham et al (2017) found any pattern of escalation in harm of domestic crime among abusers repeatedly reported to police. Where there is evidence of re-offending from these cohorts, average crime harm scores did not exceed the first-year average crime harm score; in fact, these power few offenders, as the studies described them, showed de-escalation in the severity of their offending.…”
Section: Using Crime Harm Indices To Track Offendersmentioning
confidence: 77%
“…Yet whether the concentration being described is measured by offending volume or by the sum of its severity can make a big difference in the meaning of the concept. The total volume of an individual's crimes, as recent evidence shows (Barnham et al 2017;Bland and Ariel 2015), is not a good predictor of the total harm from an individual's crimes.…”
Section: Tracking Offenders Over Timementioning
confidence: 85%
See 1 more Smart Citation
“…As pointed out by Norton et al (2018), a crime hotspot with 30 robberies in a given year is not the same as one with 30 thefts: the severity of these behaviours is not the same. In domestic violence studies, a very small subset of offenders has been found to cause the most harm to victims (Barnham, Barnes, & Sherman, 2017;Bland and Ariel 2015). Dudfield et al (2017) have shown that fewer than 5% of victims suffer 85% of the harm, with sex offences and robbery contributing almost two-thirds of total harm (63%).…”
Section: The 'Power Few' Of the Targeting Of The Most Harmful Offendersmentioning
confidence: 99%
“…One reason may be that most IPV cases have no repetition reported to police (Bland and Ariel 2015;Barnham et al 2017). Because the likelihood of further violence reported to police increases with the number of priors, it seems likely that a programme targeted on dyads with repeated reports to police might have a greater chance of showing a measurable effect.…”
Section: Introductionmentioning
confidence: 99%